Enhanced anti-tumor efficacy of paclitaxel with PEGylated lipidic nanocapsules in presence of curcumin and poloxamer: In vitro and in vivo studies. (November 2016) - Anwar, Mohammed; Akhter, Sohail; Mallick, Neha; Mohapatra, Sharmistha; Zafar, Sobiya; Rizvi, M. Moshahid A.; Ali, Asgar; Ahmad, Farhan J..
Graphical abstract: Abstract: Cancer chemotherapeutic drug containing PEGylated lipidic nanocapsules (D-LNCs) were formulated by the controlled addition of organic phase (combined solution of paclitaxel and curcumin in a mixture of oleic acid and MPEG2000 -DSPE (90:2.5 molar ratio) in acetone) to the aqueous phase (consist of Poloxamer 407 as emulsifying agents and glycerol as a co-solvent) at a temperature of 55–60 °C followed by evaporation of organic solvent. The obtained pre-colloidal dispersion of D-LNCs was processed through high pressure homogenization to get more uniformly and nano-sized particles. Effect of concentration of emulsifying agent and process variables of high pressure homogenization (pressure and number of cycles) on average particle size and entrapment efficiency was further investigated by constructing Box–Behnken experimental design to achieve the optimum manufacturing process. D-LNCs were characterized by dynamic light scattering, scanning and transmission electron microscopy, Fourier transform infrared spectroscopy, and differential scanning calorimetry. In vitro release studies showed a sustained release pattern of drug from the PEGylated D-LNCs, whereas in vivo pharmacokinetic studies after a single-dose intravenous (i.v.) administration of paclitaxel (15 mg/kg) in Ehrlich ascites tumor (EAT)-bearing female Swiss albino mice showed a prolonged circulation time and slower elimination of paclitaxel from D-LNCs as compared with marketed formulation (Paclitec ® ). From the plasma concentration vs. time profile, i.v. bioavailability (AUC0-∞ ) of paclitaxel from D-LNCs was found to be increased approximately 2.91-fold (P < 0.001) as compared to Paclitec ® . In vitro cell viability assay against MCF-7 and MCF-7/ADR cell lines, in vivo biodistribution studies and tumor inhibition study in EAT-bearing mice, all together prove its significantly improved potency towards cancer therapy.